Metals pollution in tropical Wetlands - Yunus, Kamaruzzaman (intechopen, 2019)
Metals pollution has drawn worldwide attention due to increase of anthropogenic contaminants to the coastal area, especially wetlands area. Metals are indestructible and have toxic effects on living organisms. Sediment can act as an indicator of metals pollution due to the ability of the sediment that can trap metals through complex physical and chemical process. Therefore, they are always used as geo-marker for identifying the possible source of metals pollution. Besides that, wetlands such as mangrove have a diverse diversity of organisms that provide proteins to local communities such as clam, oyster, crab, and fishes. Therefore, it is important for us to know the levels of metals in the sediment and those organisms that we consume nowadays that live at the mangrove area. Such findings can provide important information on the seafood safety level and potential impact especially to humans via consumption according to the provisional tolerable weekly intake and daily intake.